2016
DOI: 10.5005/jp-journals-10005-1323
|View full text |Cite
|
Sign up to set email alerts
|

Primary Dentition Analysis: Exploring a Hidden Approach

Abstract: Background: Accurate prediction of the mesiodistal widths (MDWs) of canines and premolars in children with primary dentition facilitates interception of malocclusion at an early age. Boston University (BU) approach is one, i.e., based on primary teeth for predicting canine and premolar dimensions.Aim: To predict the canine and premolar dimensions, in the contemporary population, using BU approach and compare with the values obtained using Tanaka-Johnston (T/J) approach.Design: Children in the age range of 7-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In this study, it was found that there was a statistical significance between the measurements of the mesiodistal widths of males and females. This is in line with a study conducted by Grover et al and Nuvvula et al 6 , 27 In this study, it was found that Tanaka–Johnston's method tended to overestimate the mesiodistal widths of both the maxilla and the mandible for females as it had statistical significance with a p value less than 0.001. This is similar to a study conducted by Grover et al, wherein both the maxillary and mandibular arches in the females had values higher predicted values than the actual values.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, it was found that there was a statistical significance between the measurements of the mesiodistal widths of males and females. This is in line with a study conducted by Grover et al and Nuvvula et al 6 , 27 In this study, it was found that Tanaka–Johnston's method tended to overestimate the mesiodistal widths of both the maxilla and the mandible for females as it had statistical significance with a p value less than 0.001. This is similar to a study conducted by Grover et al, wherein both the maxillary and mandibular arches in the females had values higher predicted values than the actual values.…”
Section: Discussionsupporting
confidence: 91%
“…Prediction of width of permanent canines and premolars can be done as early as in primary dentition using Boston University approach but the clinical implication of this prediction is undermined by the changes in arch dimensions, tooth position and inclination. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%